The real terror of Instagram: Death and disindividuation in the social media scopic field. (December 2019) - Crano, Rd
In a 1980 interview, Roland Barthes attests that 'what is terrible about a photograph is that there is no depth in it, that it is clear evidence of what was there'. In the social media age, photographic equivalents of sound bites pass between users and groups for mere seconds before they leave forever one's field of vision. To what extent is it still possible to be wounded by a photograph in the ways Barthes famously described? This essay proposes to explicate some of the psychological and sociopsychological effects of networked images, specifically as they have come to play an increasingly essential role in peer-to-peer and small group communications. As smartphone technologies and data-processing speeds have improved, virtual communities have come to form around and communicate largely through photographs. This essay first considers the evolving nature of subjectivity and otherness in this new era of selfies and self-spun spectacle; it then revisits Lacan's dialectic of eye and gaze to further assess the radical reconfiguration of self and society at stake in the social media imagescape. Platforms like Facebook, Snapchat, and Instagram force us to rethink some of psychoanalysis' long heralded heuristics for understanding vision and visuality; at the same time, however, these same heuristics can provide a critical groundwork for recognizing what, indeed, is so 'terrible' – and terrifying – about this new cult of the image.